How do rest-pause and sarcoplasma stimulating training models affect metabolic and psychoaffective responses in bodybuilding athletes compared to traditional training? - Almeida, Gustavo P. L.; João, Gustavo A.; Charro, Mário A.; de Jesus Santana, Wilian; da Silva, Carlos Eduardo Rosa; Bocalini, Danilo S.; Caperuto, Érico C.; Figueira, Aylton J. (Frontiers in Sports and Active Living, 2024)
Introduction Strength training (ST) is a strategy to enhance quality of life through increased strength, muscle hypertrophy, and functional capacity. Training systems are associated with manipulation of volume and intensity, generating different stimuli, such as Rest-Pause (RP) and Sarcoplasmic Stimulating Training (SST). These systems induce greater mechanical and physiological stress, leading to increased strength and muscle hypertrophy. However, the metabolic and psycho-affective effects of advanced systems in experienced practitioners remain inconclusive. The purpose of the study is to analyze the acute effects of RP, SST, and Traditional (TMS) systems on metabolic and psycho-affective responses in adult men. Methods This experimental crossover study assessed 15 subjects (30.38 ± 2.06 years; 88.40 ± 6.50 kg; 1.74 ± 0.07 cm) experienced in ST, evaluated under TMS, RP, and SST during flat bench press and leg press 45° exercises. Body composition, muscular strength via 1-RM testing, lactate concentration (LAC), and psycho-affective measures (Rating of Perceived Exertion-RPE; Visual Analog Scale-VAS; Feeling Scale-FS) were determined. Statistical analysis was performed using the Minitab software, with p ≤ 0.05, IC-95%). Results The finals results showed SST exhibited a 38.10% lower LAC concentration post-training session compared to TMS, while RP showed 37.20% lower LAC concentration than TMS post-session. Average RPE values for RP and SST were higher (8.50 ± 1.10 and 8.60 ± 0.90, respectively) than TMS (6.00 ± 1.10). VAS displayed higher average values for RP and SST (8.00 ± 2.00 and 8.00 ± 1.00, respectively) compared to TMS (5.00 ± 1.00), with affective ratings indicating positive values for TMS and values between 0 and −5 for RP (40%) and SST (60%) post-training sessions, suggesting that RP and SST induced less affective response than TMS. Discussion The results lead to the conclusion that manipulation of training volume and intensity led to higher RPE and pain (VAS). The data suggest that inappropriate prescription of these systems could lead to greater displeasure, leading us to hypothesize that a higher likelihood of discontinuation from strength training programs would occur, suggesting that greater repetition volumes (RP and SST) should be targeted at individuals with a higher training level.